TEK FAZLI GERİLİM KAYNAKLI EVİRİCİLERDE HARMONİK ELİMİNASYONU İÇİN YENİ BİR YAKLAŞIM - SÜNTER, ZELİHA (Fırat Üniveristesi, 2013)
Bu tez çalışmasında ilk olarak tek fazlı bir eviricinin iki farklı modülasyon algoritması kullanılarak modellenmesi ve benzetimi yapılmıştır. Tek fazlı eviricilerin devre yapısı verilmiş ve çalışması farklı yük karakteristiklerine göre analiz edilmiştir. Frekans ve gerilim yöntemleri olan kısmi kare dalga modülasyon algoritması ve darbe genişlik modülasyon algoritması açıklanarak bu algoritmalar tek fazlı eviriciye uygulanmıştır. Matlab/Simulink kullanılarak evirici modellenmiş ve iki modülasyon algoritmalarına göre benzetim sonuçları alınmıştır. Değişik modülasyon indekslerinde ve çıkış frekanslarında alınan benzetim sonuçları aynı şartlar için kısmi kare dalga ve darbe genişlik modülasyon teknikleri kullanılarak karşılaştırılmıştır. Bu tezde tek fazlı eviriciler için kısmi kare dalga yönteminin özel bir uygulaması olan yeni bir kontrol yöntemi önerilmiştir. Bu yöntem V/f kontrollü olarak bir çıkış periyodunda minimum anahtarlama ile evirici çıkışında kısmi kare dalga yöntemine kıyasla daha az harmonik içeriğine sahip bir dalga şekli üretmektedir. Önerilen yöntemin ve kısmi kare dalga yönteminin Matlab/Simulink'te modelleri kurulmuş ve aynı şartlarda ve değişik çıkış frekanslarında açık çevrim V/f kontrollü olarak karşılaştırmalı benzetim sonuçları verilmiştir. Önerilen yöntemin üstünlüğü dalga şekilleri ve harmonik spektrumları ile gösterilmiştir.

In this thesis firstly, modeling and simulation of a single-phase inverter has been performed by using two different modulation algorithms. Circuit structure of a single-phase voltage source inverter has been given and its operation has been analyzed for various load characteristics. Quasi square wave and pulse width modulation (PWM) algorithms which are used as voltage and frequency control methods in inverters have been demonstrated and applied to the single-phase inverter. The inverter has been modeled in Matlab/Simulink and simulation results have been taken for two modulation algorithms. Simulation results which are taken for various modulation indexes and output frequencies have been compared for the same operating conditions. In this thesis, a novel control technique which is a particular implementation of the quasi square wave method has been proposed for the single-phase voltage source inverter. This method produces V/f controlled voltage waveform at the output with low harmonic content comparing to the quasi square wave modulation technique. In addition the semiconductor devices in the inverter turns on and off only once in one output period resulting in minimum switching losses. Matlab/Simulink models of the proposed system and the inverter system with quasi square wave modulation technique have been obtained. The comparative simulation results for both techniques are given at various output frequencies. Open-loop V/f control has been applied to both inverters. Superiority of the proposed technique to the classical quasi square wave modulation technique has been shown with the output waveforms and their spectra.
A new approach for harmonic elimination in single-phase voltage source inverters
Keywords: Elektrik ve Elektronik Mühendisliği